Testsite for traffic detectors, setup and results - Roslyng, Thomas Westring (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
Traffic measurements are of crucial importance for traffic management systems. It is necessary that within a few seconds measure for example speed and dangerous traffic situations to be able to warn the road user on variable message signs (VMS) or inform through other forms of media. These measurements are useful also for a broader knowledge about traffic development and congestion problems. A test site on one of the major roads enables the Road Directorate to try out new equipment and technologies. Experience has shown that it is difficult by normal tender procedures to secure that the selected type of detectors are the right ones. Among other things, determination of the detector accuracy can be accomplished only when it is finally adjusted to the traffic management system. Furthermore, it is necessary to get experience about operation to lay down the requirement for maintenance and adjustment needs. Therefore, the Road Directorate has found it necessary to set up a test site in order to be able to test traffic detectors before deciding what to procure.